The greatest hoax on earth?: refuting Dawkins on evolution; a response to Richard Dawkins' The greatest show on earth, the evidence for evolution - Sarfati, Jonathan (Creation Book Publ., 2010)
Bait-and-switch -- Species and kinds -- Natural selection -- Evolution before our very eyes? -- Embryos and self-assembly -- Common ancestry or common design? -- Where are the transitional fossils? -- The links are still missing -- Ape-men? -- Geographical distribution -- Is the earth ancient? -- Young world evidence -- Origin of life -- Lost structures : evolution or devolution? -- 'Bad design' : evidence for evolution? -- "Nature, red in tooth and claw" -- Evolution, science, history and religion